THE GROUND OF EVIDENCE-BASED MEDICINE IN ONCOLOGY (THE LECTURE) - D. L. Speransky; A. Yu. Nenarokomov (Креативная хирургия и онкология, 2017)
This lecture  is devoted to  problems of  usage   of  evidence-based medicine  rules  in oncologic researches. The basic criteria of evidential standards in oncology were presented. Authors pointed out the general  recommendations for planning, realization  and analyze of results of researches.